A new PAPR reduction in OFDM systems using PTS combined with APPR for TWTA nonlinear HPA - Pradabpet, Chusit; Dejhan, Kobchai (My University, 2008)
In this paper, we propose a new Peak-to-Average Power Ratio (PAPR) reduction technique using a partial transmit sequence (PTS) combined with adaptive peak power reduction (APPR) methods. This technique is used in a system based on Orthogonal Frequency Division Multiplexing (OFDM). In order to reduce PAPR, the sequence of input data is rearranged by the PTS for the reduction of PAPR and then fed to the APPR process in the proposed system. The APPR method controls the peak level of the modulation signal by an adaptive algorithm. The proposed method shows the improvement on PAPR, on the power spectrum density (PSD) and on the high performance on bit error rate (BER) of an OFDM system.
Keywords: Adaptive peak power reduction (APPR); Nonlinear HPA; OFDM; PAPR; PTS